Analisis Kinerja Pengendali Kaskade Pada Sistem Load Frequency Control (LFC) Hidraulik Menggunakan PIDTune Model Standard - Laksono, Heru Dibyo; Putri, Dhea Rahmadani; Muharam, mumuh; Pratama, Rizki Wahyu; Nofendra, Riko (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2025)
This study evaluates the performance of a hydraulic Load Frequency Control (LFC) system using cascade controllers in various configurations with and without droop characteristics. Through MATLAB simulation, several types of controllers such as P, PI, PD, PID, PDF, and PIDF are analysed to measure transient response parameters such as rise time, peak time, steady state time, and overshoot. The results show that the droop configuration provides better performance, with faster response and reduced oscillation compared to the other configurations. The use of filters in PIDF and PDF controllers is very effective in dampening high frequency disturbances and improving system stability. The PDF and PIDF controllers, thanks to their derivative components, showed the best performance with fast response times and minimal overshoot. Overall, droop configurations, especially with PDF controllers, are recommended to maintain frequency stability in hydraulic LFC systems, especially under dynamic load conditions.